TEACHER'S READINESS IN LEARNING MARITIME MATERIALS - Seno Budhi Ajar; Gentur Adi Tjahjono (Universitas Sebelas Maret (UNS), 2020)
The purpose of this study is to find out: (1) teacher's level of understanding of maritime material, (2) the ability of teachers in the preparation of maritime learning media, (3) student acceptance of maritime learning. This type of research is qualitative with the research method used is the sample survey method. The study population was all Social Sciences Junior High School Teachers in Surakarta. Samples were taken at random as many as 36 ips teachers both from public and private junior high schools in Surakarta. Data collection techniques with questionnaires and documentation. Based on research results obtained by the level of understanding of maritime teachers as much as 79% are at a medium level, as well as the level of teacher's ability to make maritime learning media as much as 61% are in the medium level so that student acceptance of maritime learning as much as 66% is in the medium level.